Cyanidin-3-glucoside: targeting atherosclerosis through gut microbiota and anti-inflammation - Tang, Zihan (Frontiers in Nutrition, 2025)
With the shifting global disease spectrum, atherosclerosis (AS) has emerged as a leading contributor to mortality worldwide, with associated cardiovascular diseases (CVDs) representing the predominant cause of death. AS, a chronic inflammatory pathology, is mechanistically linked to oxidative stress and gut microbiota dysbiosis, which drive excessive reactive oxygen species (ROS) production and elevated levels of pro-inflammatory cytokines. Dietary polyphenols, particularly anthocyanins, are well-characterized for their dual role in modulating gut microbial communities and ameliorating chronic inflammatory conditions. Cyanidin-3-glucoside (C3G), a water-soluble flavonoid abundant in pigmented fruits and vegetables, exhibits potent antioxidant, anti-inflammatory, and anti-hypertensive bioactivities. More importantly, C3G engages in bidirectional interactions with the gut microbiota. It alters microbial composition and undergoes bacterial enzymatic metabolism to generate phenolic derivatives, including protocatechuic acid (PCA), which demonstrate enhanced systemic bioavailability and bioactivity. These metabolites improve endothelial function by augmenting nitric oxide (NO) bioavailability through endothelial nitric oxide synthase (eNOS) activation and regulating lipid homeostasis through ATP-binding cassette transporter G1 (ABCG1)-mediated pathways. Therefore, this review describes the dual mechanistic role of C3G as a phenolic bioactive compound and a prebiotic modulator, highlighting its therapeutic potential in chronic disease prevention through microbiota-dependent and -independent pathways. These insights underscore the need for advanced mechanistic studies to identify specific bacterial taxa involved in C3G biotransformation and to optimize targeted delivery systems to maximize their therapeutic efficacy.